Incidencia de la asistencia técnica en la administración de las entidades territoriales certificadas a través de la estrategia de gestores en el sistema educativo colombiano (2014)
The Colombian educational system for the provision of public education services in preschool, primary, secondary, primary and middle, has established guidelines and policies, directed by the Ministry of National Education -MEN-, in order to ensure access of people and the retention of students in the classroom. To achieve this end, the decentralization of the education sector, meaning the direct administration of the service by the local authority, creates strategies and projects to improve the management of certified education secretariats. That is why in 2002 the strategy of managers in education is created depending directly on the Minister to organize the sector and provide differentiated support to local authorities -ETC- certified. With the passage of time and the current administration of -MEN-, this strategy has been assigned to the sub institutional strengthening component is part of the technical assistance system, allowing the Ministry of Education to provide advice to the various local authorities creating their diagnosis, management of financial and human resources, information management registration and use of technological tools. Technical assistance working with local authorities in implementing planning processes and management